The influence of demographic factors onto the ethical behaviours of supporting officers in the Immigration Department of Malaysia / Asmidar Lokman … [et al.] - Lokman, Asmidar; Talib, Ahmad Tarmizi; Ahmad, Zaid; Jawan, Jayum (Faculty of Administrative Science & Policy Studies (FASPS), Universiti Teknologi MARA (UiTM) Shah Alam, 2018)
Previous studies found that demographic factors influence the ethical behaviour of people. The demographic factors most researched are on age, gender, and years of service. However, those studies showed mixed results. Therefore, the purpose of this study is to assess the influence of the demographic profile on the ethical behaviour. This study specifically focused on bribery as one form of behaviour. A cross sectional study among Malaysian Immigration Department’s supporting officers of Putrajaya and Kuala Lumpur was done using the questionnaire survey. The survey also have targeted towards the supporting officers from the work grade of KP17, KP22, and KP26 from five operational divisions. The results were analyzed using SPSS version 21. An independent t–test and ANOVA analysis were conducted to determine the influence of age, gender, and years of service onto ethical behaviour of the supporting officers. The results showed that the supporting officers ‘ethical behaviour is not influenced by their gender, age, or their years of service as both men and women have approximately equal tendencies to behave ethically and unethically.